Best available techniques and the value chain perspective. (10th February 2018) - Huybrechts, D.; Derden, A.; Van den Abeele, L.; Vander Aa, S.; Smets, T.
Abstract: During the past decades, the concept of best available techniques (BAT) has evolved as a reference point for setting environmental permit conditions. As all environmental regulations, BAT-based permit regulations can potentially act as a driver or as a barrier for greening global value chains and for implementation of sustainable supply chain management and circular economy. Whether they will effectively act as a driver or as a barrier for these, depends on if and how up- and downstream activities are considered in the determination of BAT at the sector level on the one hand, and on the way BAT are implemented at the installation level on the other hand. In existing methods for determination of BAT at the sector level, the focus of the assessment is generally on the sector under consideration, without explicit or systematic consideration of up- and downstream activities. The purpose of this paper is to investigate if and how up- and downstream activities have been considered in the determination of BAT in practice, more specifically in the Sevilla process for information exchange on BAT in the context of the European Industrial Emission Directive. The assessment is based on a review of BAT reference documents, using a case study approach involving 4 case studies, each addressing a particular value chain aspect (i.e. an existing interaction between upstream and downstream activities), and the BAT reference documents for 2 activities (1 upstream and 1 downstream) involved in the value chain aspect. The cases studied show that in the Sevilla process, examples exist where value chain aspects were considered in the determination of BAT, either by considering them as 'cross-sector effects', or by determining 'value chain BAT', for example collaboration with upstream and downstream partners in the value chain. Consideration of value chain aspects in determination of BAT is however not a systematic practice. In order for BAT based permit regulations to act as a potential driver - and not as a potential barrier - for greening global value chains, 3 complementary approaches for a more systematic consideration of value chain aspects in the BAT determination process are proposed: consideration of relevant 'cross-sector effects', determination of 'value chain BAT' and selection of 'collaboration with upstream and downstream partners in the value chain' as a general BAT for all sectors. In order to incorporate these concepts in the existing methods for determination of BAT at the sector level, directions for further development of the methods were proposed. An assessment of BAT implementation practices with respect to value chain aspects was outside the scope of this paper, but is suggested as a topic for further research on the role that environmental laws and regulations, in this case BAT based permit regulations, can play in the successful implementation of sustainable supply chain management and circular economy. Highlights: Value chain aspects are not systematically considered in the determination of BAT. Options for considering value chain aspects in the determination of BAT are proposed. BAT can be a potential driver for greening global value chains.